2018
DOI: 10.3389/fonc.2018.00211
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus Epidemiology, Serology, and Genetic Variability of LMP-1 Oncogene Among Healthy Population: An Update

Abstract: The Epstein–Barr virus (EBV) is a DNA lymphotropic herpesvirus and the causative agent of infectious mononucleosis. EBV is highly prevalent since it affects more than 90% of individuals worldwide and has been linked to several malignancies including PTLDs, which are one of the most common malignancies following transplantation. Among all the EBV genes, most of the recent investigations focused on studying the LMP-1 oncogene because of its high degree of polymorphism and association with tumorigenic activity. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 148 publications
(247 reference statements)
9
210
1
10
Order By: Relevance
“…There are two main EBV genotypes, type 1 and type 2, distinguished by the differences in EBNA‐2 gene, which can further be subdivided into different virus strains . Type 1 is prevalent in population from Europe, America, China and South Asia, while type 2 is more observed in African and Papua New Guinean populations, where it shares an equal distribution with type 1.…”
Section: Open Questions and Discussionmentioning
confidence: 99%
“…There are two main EBV genotypes, type 1 and type 2, distinguished by the differences in EBNA‐2 gene, which can further be subdivided into different virus strains . Type 1 is prevalent in population from Europe, America, China and South Asia, while type 2 is more observed in African and Papua New Guinean populations, where it shares an equal distribution with type 1.…”
Section: Open Questions and Discussionmentioning
confidence: 99%
“…In some cases, EA (D) IgG is detectable several years after a primary infection. High titers of EA (D) IgG, VCA and EA IgA have been observed in patients with NPC [44][45][46].…”
Section: Ebv Serologymentioning
confidence: 99%
“…However, only a few have generally been investigated and utilized for diagnostic purposes [9]. It has been shown that anti-EA antibodies (EA immunoglobulin G (IgG)) are of two forms; EA-diffuse (D) IgG, which increases within three-to-four weeks and could remain until three-to-four months, and EA-restricted (R) IgG, which may remain at a high level for up to two years [9,44]. In some cases, EA (D) IgG is detectable several years after a primary infection.…”
Section: Ebv Serologymentioning
confidence: 99%
See 2 more Smart Citations